Virtual reality sickness questionnaire (VRSQ): Motion sickness measurement index in a virtual reality environment. (May 2018) - Kim, Hyun K.; Park, Jaehyun; Choi, Yeongcheol; Choe, Mungyeong
Abstract: This study aims to develop a motion sickness measurement index in a virtual reality (VR) environment. The VR market is in an early stage of market formation and technological development, and thus, research on the side effects of VR devices such as simulator motion sickness is lacking. In this study, we used the simulator sickness questionnaire (SSQ), which has been traditionally used for simulator motion sickness measurement. To measure the motion sickness in a VR environment, 24 users performed target selection tasks using a VR device. The SSQ was administered immediately after each task, and the order of work was determined using the Latin square design. The existing SSQ was revised to develop a VR sickness questionnaire, which is used as the measurement index in a VR environment. In addition, the target selection method and button size were found to be significant factors that affect motion sickness in a VR environment. The results of this study are expected to be used for measuring and designing simulator sickness using VR devices in future studies. Highlights: A questionnaire about motion sickness in virtual reality environment was developed. The existing simulator sickness questionnaire was modified to develop the virtual reality sickness questionnaire (VRSQ). The newly derived VRSQ consisted of 9 items, which are included in two components, namely oculomotor and disorientation.